2023
DOI: 10.1071/ch23042
|View full text |Cite
|
Sign up to set email alerts
|

Highly accurate CCSD(T) homolytic Al–H bond dissociation enthalpies – chemical insights and performance of density functional theory

Abstract: We obtain gas-phase homolytic Al–H bond dissociation enthalpies (BDEs) at the CCSD(T)/CBS level for a set of neutral aluminium hydrides (which we refer to as the AlHBDE dataset). The Al–H BDEs in this dataset differ by as much as 79.2 kJ mol−1, with (H2B)2Al–H having the lowest BDE (288.1 kJ mol−1) and (H2N)2Al–H having the largest (367.3 kJ mol−1). These results show that substitution with at least one –AlH2 or –BH2 substituent exerts by far the greatest effect in modifying the Al–H BDEs compared with the BDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…In contrast, the worst-perfo method was shown to be the HGGA functional BH&HLYP, which afforde unacceptably large MAD of 45.6 kJ mol −1 and an LD of 54.2 kJ mol −1 . The poor perform of BH&HLYP in the computation of BDEs has been noted previously, for examp computation of Al-H [48], B-Cl [49], and N-X (X = F, Cl, and Br) bonds [54,55]. Seco all but four cases, it is evident that the functionals considered in this study te underestimate the BDEs (i.e., the MD values adopt negative values in most cases).…”
Section: Performance Of Dft Methods For Computing B-f Bdessupporting
confidence: 49%
See 2 more Smart Citations
“…In contrast, the worst-perfo method was shown to be the HGGA functional BH&HLYP, which afforde unacceptably large MAD of 45.6 kJ mol −1 and an LD of 54.2 kJ mol −1 . The poor perform of BH&HLYP in the computation of BDEs has been noted previously, for examp computation of Al-H [48], B-Cl [49], and N-X (X = F, Cl, and Br) bonds [54,55]. Seco all but four cases, it is evident that the functionals considered in this study te underestimate the BDEs (i.e., the MD values adopt negative values in most cases).…”
Section: Performance Of Dft Methods For Computing B-f Bdessupporting
confidence: 49%
“…As previous studies have shown that the inclusion of empirical dispersion corrections may improve the performance of the underlying DFT functionals for the computation of various BDEs [48,49,55], we have additionally surveyed the effect of the inclusion of the Becke-Johnson D3 dispersion correction for twelve functionals (Table 4).…”
Section: Performance Of Dft Methods For Computing B-f Bdesmentioning
confidence: 99%
See 1 more Smart Citation